2018
DOI: 10.18632/oncotarget.26494
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 3 subunit C is associated with acquired resistance to erlotinib in non-small cell lung cancer

Abstract: The acquisition of resistance to EGFR tyrosine kinase inhibitors (EGFR-TKIs) is one of the major problems in the pharmacotherapy against non-small cell lung cancers; however, molecular mechanisms remain to be fully elucidated. Here, using a newly-established erlotinib-resistant cell line, PC9/ER, from PC9 lung cancer cells, we demonstrated that the expression of translation-related molecules, including eukaryotic translation initiation factor 3 subunit C (eIF3c), was upregulated in PC9/ER cells by proteome ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…PGRMC1 contributes to acquired resistance to erlotinib. To elucidate the molecular mechanism of acquired EGFR-TKI resistance, we previously compared PC9 and PC9/ER cells by proteomics analysis 13 ; the results indicated that PGRMC1 expression in PC9/ER cells was 3.8-fold that in PC9 cells (Table 1). To validate the clinical relevance of PGRMC1, Kaplan-Meier plots regarding PGRMC1 expression and overall survival in the lung cancer revealed that high expression of PGRMC1 patients have less overall survival rate than low expression of PGRMC1 patients (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGRMC1 contributes to acquired resistance to erlotinib. To elucidate the molecular mechanism of acquired EGFR-TKI resistance, we previously compared PC9 and PC9/ER cells by proteomics analysis 13 ; the results indicated that PGRMC1 expression in PC9/ER cells was 3.8-fold that in PC9 cells (Table 1). To validate the clinical relevance of PGRMC1, Kaplan-Meier plots regarding PGRMC1 expression and overall survival in the lung cancer revealed that high expression of PGRMC1 patients have less overall survival rate than low expression of PGRMC1 patients (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By performing proteome analysis with a newly established erlotinib-resistant cell line, PC9/ER, derived from PC9 lung cancer cells 13 , we previously revealed progesterone membrane component 1 (PGRMC1) as a candidate protein involved in acquired resistance to erlotinib. Recently, PGRMC1 was reported to be overexpressed in breast cancer 14 , lung cancer 15 , and ovarian cancer 16 .…”
mentioning
confidence: 99%
“…Erlotinib, an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is an oral targeted anticancer drug for non-small cell lung cancer (NSCLC) treatment, and showing a significant improvement of survival in NSCLC [ 32 ]. However, erlotinib-acquired resistance is a tough obstacle to effectively treating NSCLC patients with EGFR mutant characteristics [ 33 35 ]. The mechanism underlying erlotinib resistance in NSCLC has not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxic melanoma EVs carried a hypoxic signature consisting of six proteins (AKR7A2, DDX39B, EIF3C, FARSA, PRMT5, VARS) which were significantly associated with a poor prognosis for melanoma patients. EIF3C promotes proliferation, migration and invasion of prostate [46], ovarian and hepatocellular carcinoma cells [47,48] and was associated with resistance to erlotinib in lung cancer [49]. PRMT5 (Protein arginine methyltransferase 5) is upregulated under hypoxia [50] and has many roles in cancer [51].…”
Section: Discussionmentioning
confidence: 99%